Truth, Truth-telling and Gender in Politics: The ”Hillary” Experience - C. Akça Ataç (European Journal of American Studies)
Among the highest goals to be achieved by political feminism, a female US president has held an elusive but prominent place. Hillary Clinton’s 2016 presidential campaign, which coincided with Wonder Woman’s new post as the United Nations ambassador, has been the closest moment for this goal to be achieved. Clinton’s inattention to truth-telling, the email interrogation pursued by the FBI against her and her failure to win the election, however, have in part resulted in the passing of that moment. This study, on this account, probes Hillary Clinton’s candidacy for president in terms of women’s historical relation with truth-telling and feminist standpoint. It argues that if Clinton had been more committed to the truth-telling principles and practices, her presidential campaign would have been a substantial contribution to historical and political feminism.